Anti-PD-1 Therapy Response Predicted by the Combination of Exosomal PD-L1 and CD28 - Zhang, Chaoxu; Fan, Yibo; Che, Xiaofang; Zhang, Min; Li, Zhi; Li, Ce; Wang, Shuo; Wen, Ti; Hou, Kezuo; Shao, Xinye; Liu, Yunpeng; Qu, Xiujuan (Frontiers in Oncology, 2020)
Anti-PD-1 therapy has been approved for cancer treatment. However, the response rate is unsatisfactory. The expression of PD-L1 in tumor tissues is unreliable to predict the treatment response. Recent studies suggested that exosomal PD-L1 not only exerts immunosuppressive effects but also plays a significant role in the development of tumor microenvironment. Thus, the present study aimed to investigate exosomal PD-L1 in improving its predictive value and efficacy. A total of 44 patients with several types of advanced tumors, treated by anti-PD-1 therapy, were enrolled. Exosomes were collected and purified from plasma. The exosomal PD-L1 was detected by ELISA. The cytokines were measured by the MILLIPLEX magnetic bead assay. Compared to the responders, exosomal PD-L1 of the non-responders were significantly higher than those of the responders (P=0.010) before the treatment. Concurrently, exosomal PD-L1 and tumor burden decreased when the therapy was effective. Also, the baseline expression of CD28 was higher in the responders than non-responders (P=0.005). Univariate and multivariate analysis validated with 1000 times bootstrapping suggested that high exosomal PD-L1 and low CD28 expression were negative factors for progression-free survival (PFS) in patients who underwent anti-PD-1 treatment. The combination of exosomal PD-L1 and CD28 obtained more area under the curve (AUC) of receiver operating characteristic (ROC) (AUC 0.850 vs. 0.784 vs. 0.678) and showed a higher probability without progression via nomograph. These findings suggested that the expression of exosomal PD-L1 and CD28 could serve as the predictive biomarkers for clinical responses to anti-PD-1 treatment.